Metabolism of aflatoxin B1 by rat hepatic microsomes induced by polyhalogenated biphenyl congeners. - Halvorson, M R (1985)
The metabolism of aflatoxin B1 to aflatoxins M1 and Q1 by rat liver microsomes from animals pretreated with polychlorinated or polybrominated biphenyl congeners depended on the structure of the halogenated biphenyl inducers. Microsomes from rats treated with phenobarbital (PB) or halogenated biphenyls that exhibit PB-type activity preferentially enhanced the conversion of aflatoxin B1 to aflatoxin Q1. In contrast, microsomes from rats treated with 3-methylcholanthrene (MC) or halogenated biphenyls that exhibit MC-type induction activity increased the metabolism of aflatoxin B1 to aflatoxin M1. The coadministration of PB and MC produced microsomes that exhibited both types of induction activity (mixed type) in catalyzing the oxidative metabolism of diverse xenobiotic agents. However, PB-plus-MC-induced hepatic microsomes from immature male Wistar rats preferentially increased the metabolism of aflatoxin B1 to aflatoxin M1 but did not enhance the conversion of aflatoxin B1 to aflatoxin Q1. Comparable results were observed with microsomes from rats pretreated with halogenated biphenyls classified as mixed-type inducers; moreover, in some cases there was a significant decrease in the conversion of aflatoxin B1 to aflatoxin Q1 (compared with that of controls treated with corn oil).